[BP.11.07] LDL-OXIDATION, SERUM URIC ACID AND PULSE-WAVE VELOCITY RELATIONSHIP IN CHRONIC KIDNEY DISEASE: DATA FROM THE BRISIGHELLA HEART STUDY COHORT. (September 2017) - Cicero, A.F. G.; Bove, M.; Rosticci, M.; Fogacci, F.; Giovannini, M.; D'Addato, S.; Borghi, C.
Abstract : Objective: The aim of our study was to evaluate the relationship between oxidized LDL (oxLDL), elevated Serum Uric Acid (SUA) and arterial stiffness in subjects with normal renal function compared with subjects with mild or moderate chronic kidney disease (CKD). Figure. No caption available. Design and method: We selected from the database of the Brisighella Heart Study 205 adult non-smokers subjects, in primary prevention for cardiovascular disease, with normal renal function (M: 99, F: 106), 118 age-matched subjects with mild CKD (M: 55; F: 63) and 94 with moderate CKD (M: 44; F: 50), all visited during the 2012 population survey. All subjects underwent a medical visit including the determination of LDL oxidative susceptibility, oxLDL levels and arterial stiffness parameters such as Augmentation Index (AI) and Pulse Wave Velocity (PWV). Results: PWV was significantly increasing with the degree of CKD (Figure 1). An univariate analysis revealed a direct correlation of PWV with the main anthropometric, haemodynamic and laboratory values usually associated to higher arterial stiffness and a significant inverse correlation with LDL-C lag phase, HDL-C and apoAI (p < 0.05), either in subjects with normal renal function, or with mild or moderate CKD. In a stepwise multiple regression model we observed that in normal renal function and mild CKD groups the main predictors of PWV were age, Systolic Blood Pressure (SBP), ox-LDL, apoB and SUA (p < 0.05), while in moderate CKD group the main predictors were age, SBP and apoB, only (p < 0.05). Conclusions: In our population sample, SUA and oxLDL are significantly related to PWV in subjects with normal renal functions and with mild CKD, but not in subjects with more advanced CKD.